Blood Urine Nitrogen Trajectories of Acute Pancreatitis Patients in Intensive Care Units - Wang Z; Wang W; Wang M; He Q; Xu J; Zou K; Kang Y; Sun X (Dove Medical Press, 2024)
Zichen Wang,1- 3,* Wen Wang,1- 3,* Mingqi Wang,1- 3 Qiao He,1- 3 Jiayue Xu,1- 3 Kang Zou,1- 3 Yan Kang,4 Xin Sun1- 3 1Institute of Integrated Traditional Chinese and Western Medicine, Chinese Evidence-Based Medicine Center and Cochrane China Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China; 2NMPA Key Laboratory for Real World Data Research and Evaluation in Hainan, Chengdu, 610041, People's Republic of China; 3Sichuan Center of Technology Innovation for Real World Data, Chengdu, People's Republic of China; 4Intensive Care Unit, West China Hospital of Sichuan University, Chengdu, 610041, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan Kang; Xin Sun, Email kangyan@scu.edu.cn; sunxin@wchscu.cnObjective: To identify subclasses of acute pancreatitis (AP) patients in the intensive care unit (ICU) by analyzing blood urea nitrogen (BUN) trajectories.Methods: AP patients in West China Hospital System (development cohort) and three public databases in the United States (validation cohort) were included. Latent class trajectory modelling was used to identify subclasses based on BUN trajectories within the first 21 days after ICU admission. Clinical characteristics and outcomes were compared, and results were externally validated.Results: The study comprised 2971 and 930 patients in the development and validation cohorts, respectively, with five subclasses: Class 1 ("Moderate-azotemia, slow decreasing"), Class 2 ("Non-azotemia"), Class 3 ("Severe-azotemia, slow decreasing"), Class 4 ("Moderate-azotemia, rapid increasing"), and Class 5 ('Moderate-azotemia, slow increasing) identified. Azotemia patients showed significantly higher 30-day mortality risk in development and validation cohorts. Specifically, Class 4 patients exhibited notably highest mortality risk in both the development cohort (HR 5.32, 95% CI 2.62- 10.82) and validation cohort (HR 6.23, 95% CI 2.93- 13.22). Regarding clinical characteristics, AP patients in Class 4 showed lower mean arterial pressure and a higher proportion of renal disease. We also created an online early classification model to further identify Class 4 patients among all patients with moderate azotemia at baseline.Conclusion: This multinational study uncovers heterogeneity in BUN trajectories among AP patients. Patients with "Moderate-azotemia, rapid increasing" trajectory, had a higher mortality risk than patients with severe azotemia at baseline. This finding complements studies that solely rely on baseline BUN for risk stratification and enhanced our understanding of longitudinal progression of AP.Keywords: acute pancreatitis, BUN, trajectories analysis, ICU